A STUDY ON THE DIRECTIVE UTTERANCES IN THE ENGLISH TEXTBOOK ENTITLED ENGLISH FOR VOCATIONAL SCHOOLS - Anisa, Maya (2007)
This research is aimed at identifying the forms, finding out the speaker's intention, and clarifying the politeness pattern of directive utterances. To identifying the forms, the writer refers to the linguistic elements especially the sentence. In finding out the speaker's intention, the writer uses pragmatics analysis especially the speech act theory. In clarifying the politeness pattern, the writer refers to the face theory that is based on the politeness strategies. In collecting data, the writer uses document method by selecting the directive utterances which can be found in the data sources. The sources of the data are the English Textbook entitled English for Vocational Schools published by LP2IP Gadjah Mada Yogyakarta for the Novice and Elementary level. She finds that there are three forms of sentences used in expressing the directive utterance, namely: imperative, interrogative, and declarative forms. Related to the speaker's intention, the writer finds six kinds of directive utterances namely: commanding, requesting, inviting, suggesting, warning, and prohibiting. The politeness pattern that is used in expressing directive utterance, the writer finds that there are four politeness strategies that are applied namely: bald on record, positive politeness, negative politeness and off record strategy.